Evaluation of custom multiplex real - time RT - PCR in comparison to fast - track diagnostics respiratory 21 pathogens kit for detection of multiple respiratory viruses. Issue 1 (December 2016) - Malhotra, Bharti; Swamy, M.; Reddy, P.; Kumar, Neeraj; Tiwari, Jitendra
Abstract Background Severe acute respiratory infections in children can be fatal, rapid identification of the causative agent and timely treatment can be life saving. Multiplex real time RT-PCR helps in simultaneous detection of multiple viruses saving cost, time and labour. Commercially available multiplex real time RT-PCR kits are very expensive. Therefore the aim of the present study was to develop a cost effective multiplex real time RT-PCR for the detection of 18 respiratory viruses and compare it with anin-vitro diagnostics approved Fast Track Diagnostic Respiratory Pathogens 21 Kit (FTD). Methods Nasopharyngeal aspirates and throat swabs were collected and processed for extraction of nucleic acid using an automated extraction system and multiplex real time RT-PCR was performed using the FTD kit and a custom assay on 356 samples. Results Custom and FTD assays detected one or more respiratory viruses in 268 (75.29 %) and 262 (73.60 %) samples respectively. The concordance between the custom assay and the FTD assay was 100 % for HCoV OC43, HCoV 229E, HPIV-1, HPIV-2, HBoV, HPeV, Flu A, andInfluenza A(H1N1)pdm09 and 94.66 – 99.71 % for the remaining viruses; Flu B (99.71 %), HRV (99.71 %), HPIV-3 (98.87 %), HPIV-4 (99.43 %), HCoV NL63 (99.71 %), HMPV A/B (99.71 %), RSV A/B (94.66 %), EV (98.31 %), HCoV HKU1 (99.71 %), HAdV (99.71 %). Major discrepancy was observed for RSV A/B, which was over detected in 18 samples by the custom assay as compared to the FTD assay. The custom assay was much cheaper than the FTD assay and the time taken was only 29 min more. Conclusion The custom primer and probe mix was found to be comparable to the FTD assay with good concordance but was much cheaper and the time taken for reporting was only 29 min more. The low cost custom multiplex RT-PCR can be a useful alternative to the costly FTD kit for rapid identification of viral aetiology in resource limited settings.